Committee 'A' on Second Five Year Plan (Plan, Policy, Outlay and Allocation) Proceedings (May 18, 19 and 20, 1956) - Lok Sabha Secretariat (Lok Sabha Secretariat, 1956)
The proceedings of the Second Five-Year Plan (May 18-20, 1956) provide a detailed evaluation of India’s economic strategy following the First Plan. Key discussions emphasized accelerated industrialization, structural shifts in the workforce, and ambitious national income targets. Critical challenges included managing educated unemployment, inflation control, regional income disparities, and effective resource allocation. Financial strategies focused on deficit financing, export-import balance, and targeted investments in agriculture and rural infrastructure to ensure food security and employment. Recommendations stressed enhancing education, vocational training, public participation, and administrative efficiency. Overall, the discussions underscored the necessity of coordinated planning, flexible policy measures, and comprehensive rural-industrial integration to achieve sustainable economic growth and equitable development under the Second Five-Year Plan.
Lok Sabha Secretariat
Keywords: Second Five-Year Plan; Economic Development; Employment Generation; Industrialization; Deficit Financing; Agricultural Production; Resource Allocation; Inflation Control; Export-Import Balance; Rural Development